Understanding land tenure and the dimension of the territory: Land, territory, private property, public property and communal property - Soria Dall’Orso, Carlos Antonio Martín (2016)
The author analyzes the land tenure and size of the territory and the different perspectives of understanding the property, starting with the western angle of private property, with the individualistic nuance, through public ownership with its nuance of State resources, and finally by the idea of communal property with the collectivist hue, whose ownership lies not with the individual, or the state, but on a group previously identified as culturally consolidated.